But enough about me : a memoir - Reynolds, Burt; Winokur, Jon (G.P. Putnam's Sons, 2015)
"Reynolds has been a Hollywood leading man for six decades, known for his legendary performances, sex-symbol status, and storied Hollywood romances. In his long career of stardom ... Reynolds has seen it all. [This book] will tell his story through the people he's encountered on his amazing journey. In his words, he plans to 'call out the assholes,' try to make amends for being the asshole myself on too many occasions, and pay homage to the many heroes he has come to love and respect"-- Amazon.com.